Gross classification of solitary small hepatocellular carcinoma on preoperative computed tomography: Prognostic significance after radiofrequency ablation. Issue 4 (2nd July 2015) - Fu, Xu; Mao, Liang; Tang, Min; Yan, Xiaopeng; Qiu, Yudong; He, Jian; Zhou, Tie
Abstract : Aim: The prognostic significance of the gross classification of hepatocellular carcinoma (HCC) has been confirmed in both hepatectomy and living donor liver transplantation. However, the role of this type of classification in HCC treated with radiofrequency ablation (RFA) has rarely been reported. The aim of this study was to investigate the role of preoperative gross classification in cases of solitary small HCC treated with RFA. Methods: From January 2007 to September 2013, 103 patients with solitary small HCC treated with RFA were retrospectively reviewed. The lesions were classified into three types according to gross appearance in preoperative contrast‐enhanced computed tomography (CT) scans. Clinicopathological variables and survival information were compared among these three types. Univariate and multivariate analyses were performed to clarify the long‐term prognostic factors. Results: The group of 103 tumors comprised 34 type 1, 49 type 2 and 20 type 3 tumors. The level of preoperative serum α‐fetoprotein in the type 3 tumors was significantly higher than that in types 1 and 2 ( P < 0.05). The overall survival of the patients with type 3 HCC was the poorest among the three types. The tumor‐free survival of the patients with types 3 and 2 HCC were significantly poorer than those with type 1 ( P < 0.05). The univariate analysis showed that gross classification, α‐fetoprotein level, tumor size and degree of enhancement were poor prognostic factors. The multivariate analysis indicated that the gross classification was the only independent prognostic indicator. Conclusion: The preoperative gross classification was of great prognostic significance in solitary small HCC treated with RFA.